2022
DOI: 10.3389/fpsyg.2022.858781
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Arts-Based Interventions Delivered to Children and Young People in Nature or Outdoor Spaces: Impact on Nature Connectedness, Health and Wellbeing

Abstract: BackgroundThe time that children and young people spend in nature and outdoor spaces has decreased significantly over the past 30 years. This was exacerbated with a further 60% decline post-COVID-19. Research demonstrating that natural environments have a positive impact on health and wellbeing has led to prescription of nature-based health interventions and green prescribing, although evidence for its use is predominantly limited to adults. Growing evidence also shows the impact of arts on all aspects of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 85 publications
1
15
0
1
Order By: Relevance
“…Climate action also instills a sense of belonging to a greater cause and promotes values related to social justice (Sanson & Bellemo, 2021), and meaning-focused coping in relation to climate change has been found to promote wellbeing (Ojala, 2022). But for young people to truly benefit from climate action, they require adequate support from family, friends, school, and the broader community (Moore & Duffin, 2020; Moula et al, 2022). Instances of dismissal or backlash from adults and authorities, along with government inaction on climate change, contribute to the distress experienced by young activists (Hickman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Climate action also instills a sense of belonging to a greater cause and promotes values related to social justice (Sanson & Bellemo, 2021), and meaning-focused coping in relation to climate change has been found to promote wellbeing (Ojala, 2022). But for young people to truly benefit from climate action, they require adequate support from family, friends, school, and the broader community (Moore & Duffin, 2020; Moula et al, 2022). Instances of dismissal or backlash from adults and authorities, along with government inaction on climate change, contribute to the distress experienced by young activists (Hickman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Cohen et al [114] found that playgrounds with an increased variety of play elements had more visitors. In other scenarios, improvements to the health-promoting potential of parks may be identified, such as implementing community garden spaces, outdoor group exercise classes, art installations, and walking trails [115][116][117]. For any such interventions to be culturally relevant and address specific community needs, it is critical to engage local communities throughout the park planning and development process [118,119].…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…These can be important opportunities for self‐expression, socialisation and supporting others. Reviews on this topic have examined arts‐based interventions (Moula et al., 2022), group singing (Glew, Simonds, & Williams, 2021) and unstructured play (Lee et al., 2020). However, in general, the studies included in these reviews were of variable quality and rarely measured mental health‐related outcomes, so few conclusions could be drawn regarding their effectiveness.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…Recent systematic reviews examining the impact of interventions targeting or set in the natural environment have included a wide range of social and independent activities (e.g. green space activity, gardening and wilderness experiences) across diverse natural settings (Bray, Reece, Sinnett, Martin, & Hayward, 2022;Fyfe-Johnson et al, 2021;Moula, Palmer, & Walshe, 2022). Findings from these reviews have generally supported the effectiveness of these interventions for improving mental health outcomes.…”
Section: Community Interventionsmentioning
confidence: 99%